Reptin drives tumour progression and resistance to chemotherapy in nonsmall cell lung cancer - Mikesch, Jan-Henrik; Schwammbach, Daniela; Hartmann, Wolfgang; Schmidt, Lars H.; Schliemann, Christoph; Angenendt, Linus; Wiewrodt, Rainer; Marra, Alessandro; Thoennissen, Nils H.; Wardelmann, Eva; Köhler, Gabriele; Lenz, Georg; et al. (The European respiratory journal, 2018)
While targeted nonsmall cell lung cancer (NSCLC) therapies have improved the outcome of defined disease subtypes, prognosis for most patients remains poor. We found the AAA+ ATPase Reptin to be highly expressed in the vast majority of 278 NSCLC tumour samples. Thus, the objective of the study was to assess the role of Reptin in NSCLC.Survival analyses of 1145 NSCLC patients revealed that high RNA expression levels of Reptin are associated with adverse outcome. Knockdown of Reptin in human NSCLC cells impaired growth ex vivo and eliminated engraftment in a xenograft model. Reptin directly interacted with histone deacetylase 1 (HDAC1) as the critical mechanism driving NSCLC tumour progression. Pharmacological disruption of the Reptin/HDAC1 complex resulted in a substantial decrease in NSCLC cell proliferation and induced significant sensitisation to cisplatin.Our results identify Reptin as a novel independent prognostic factor and as a key regulator mediating proliferation and clonal growth of human NSCLC cells ex vivo and in vivo We unveil a Reptin/HDAC1 protein complex whose pharmacological disruption sensitises NSCLC cells to cisplatin, suggesting this approach for application in clinical trials.
Gesehen am 16.04.2020